Commercial relations between the Hafsids and Christian powers under the reign of al-Mustansir. Issue 4 (4th July 2021) - Valérian, Dominique
ABSTRACT: The crusade of 1270 should not undermine the importance and the significant development of trade relations with Christian powers during the reign of al-Mustansir. Tunis had already, since the twelfth century, a tradition of trade with Italian city-states such as Genoa, Pisa or Venice, but from the middle of the thirteenth century Provencal and Catalan merchants also made of the Hafsid capital one of their most important destinations. Immediately after the end of the crusade, which can be considered – and was probably considered by many – as an anachronistic parenthesis, new peace treaties were signed with the most important Christian powers of the Mediterranean, in order to promote maritime trade. This policy had an obvious economic dimension, and contributed to the development of the city of Tunis and, more generally, of the Hafsid sultanate. But it was also a political choice: by making of Tunis a major hub in Mediterranean trade and one of the most prosperous cities of the Islamic world, the active Hafsid diplomacy reinforced the imperial and caliphal project of al-Mustansir.